Meaningful Participation Through Online Channels in Legislation Making in Indonesia via dpr.go.id Page - Soeprapto, R. Wahjoe Poernomo (TRUNOJOYO LAW REVIEW, 2024)
Public participation in the legislative process is essential in any democratic nation. Transparency and openness are vital for state administrators to facilitate community involvement in shaping government policies. The regulatory framework for community participation is established in Law No. 13 of 2022 as a direct consequence of Constitutional Court Decision No. 91/PUU-XVIII/2020, using the term "meaningful participation." Meaningful participation takes two forms: offline and online. This discussion focuses solely on the online aspect, specifically on utilising the official website of the People's Representative Council (DPR), dpr.go.id. The assessment of the dpr.go.id page indicates the DPR's commitment to fostering meaningful online participation. This study employs normative juridical research methods, utilising a statutory and conceptual approach. The findings suggest that while meaningful participation has been normatively regulated in constitutional court decisions and laws, the technical implementation to actualise these norms is lacking in practice. In the future, the DPR needs to carry out uniform terminology used by the DPR, both in-laws and on the DPR go.id page, by following the terms used in the court decision so that meaningful online participation can be realised for the public to be able to participate more meaningfully.